The mesoglea buffers the physico-chemical microenvironment of photosymbionts in the upside-down jellyfish Cassiopea sp. - Lyndby, Niclas Heidelberg; Murray, Margaret Caitlyn; Trampe, Erik; Meibom, Anders; Kühl, Michael (Frontiers in Ecology and Evolution, 2023)
The jellyfish Cassiopea has a conspicuous lifestyle, positioning itself upside-down on sediments in shallow waters thereby exposing its photosynthetic endosymbionts (Symbiodiniaceae) to light. Several studies have shown how the photosymbionts benefit the jellyfish host in terms of nutrition and O2 availability, but little is known about the internal physico-chemical microenvironment of Cassiopea during light-dark periods. Here, we used fiber-optic sensors to investigate how light is modulated at the water-tissue interface of Cassiopea sp. and how light is scattered inside host tissue. We additionally used electrochemical and fiber-optic microsensors to investigate the dynamics of O2 and pH in response to changes in the light availability in intact living specimens of Cassiopea sp. Mapping of photon scalar irradiance revealed a distinct spatial heterogeneity over different anatomical structures of the host, where oral arms and the manubrium had overall higher light availability, while shaded parts underneath the oral arms and the bell had less light available. White host pigmentation, especially in the bell tissue, showed higher light availability relative to similar bell tissue without white pigmentation. Microprofiles of scalar irradiance into white pigmented bell tissue showed intense light scattering and enhanced light penetration, while light was rapidly attenuated over the upper 0.5 mm in tissue with symbionts only. Depth profiles of O2 concentration into bell tissue of intact, healthy/living jellyfish showed increasing concentration with depth into the mesoglea, with no apparent saturation point during light periods. O2 was slowly depleted in the mesoglea in darkness, and O2 concentration remained higher than ambient water in large (> 6 cm diameter) individuals, even after 50 min in darkness. Light-dark shifts in large medusae showed that the mesoglea slowly turns from a net sink during photoperiods into a net source of O2 during darkness. In contrast, small medusae showed a more dramatic change in O2 concentration, with rapid O2 buildup/consumption in response to light-dark shifts; in a manner similar to corals. These effects on O2 production/consumption were also reflected in moderate pH fluctuations within the mesoglea. The mesoglea thus buffers O2 and pH dynamics during dark-periods.